Clinical Benefit of Maintenance Therapy for Advanced Biliary Tract Cancer Patients Showing No Progression after First-Line Gemcitabine Plus Cisplatin - Hyung, Jaewon; Kim, Bumjun; Yoo, Changhoon; Kim, Kyo-pyo; Jeong, Jae Ho; Chang, Heung-Moon; Ryoo, Baek-Yeol (Cancer research and treatment, 2019)
Gemcitabine plus cisplatin (GemCis) is the standard first-line chemotherapy for patients with advanced biliary tract cancer (BTC). In ABC-02 study, the BTC patients received up to 6-8 cycles of 3-weekly GemCis; however, those without progression often receive more than 6-8 cycles. The clinical benefit of maintenance treatment in patients without progression is uncertain. Advanced BTC patients treated with GemCis between April 2010 and February 2015 at Asan Medical Center, Seoul, Korea, were retrospectively analysed. The patients without progression after 6-8 cycles were stratified according to further treatment i.e., with or without further cycles of GemCis (maintenance vs. observation groups). The primary endpoint was overall survival (OS) and progression-free survival (PFS). Among the 740 BTC patients in the initial screen, 231 cases (31.2%) were eligible for analysis (111 in the observation group, 120 in the maintenance group). The median OS from the GemCis initiation was 20.5 months (95% confidence interval [CI], 15.4 to 25.6) and 22.4 months (95% CI, 17.0 to 27.8) in the observation and maintenance groups, respectively (p=0.162). The median PFS was 10.4 months (95% CI, 7.0 to 13.8) and 13.2 months (95% CI, 11.3 to 15.2), respectively (p=0.320). GemCis maintenance is not associated with an improved survival outcome.